2012
DOI: 10.1159/000342354
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Scavenger Receptor MARCO and Its Association with Chronic Obstructive Pulmonary Disease and Lung Infection in 10,604 Individuals

Abstract: Background: MARCO (macrophage receptor with collagenous structure) is a dominant receptor for unopsonized particles and bacteria in the lungs. Reduced function of this receptor due to genetic variation may be associated with susceptibility to chronic obstructive pulmonary disease (COPD) and lung infection. Objectives: To identify novel genetic variants in MARCO that are associated with reduced lung function, or increased risk of COPD or lung infection. Methods: We first screened 760 individuals with extreme lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The MARCO promoter SNP increased the risk for severe RSV disease by approximately 62%. A previous investigation tested whether 9 non-synonymous coding variants or tag SNPs in MARCO associated with chronic obstructive pulmonary disease and found no association, although one of the SNPs (rs41279766) associated with the risk of sepsis ( Thomsen et al, 2013 ). Another study found tag SNPs associated with increased risk of pulmonary tuberculosis, while another was associated with resistance ( Bowdish et al, 2013 ), thus the role of MARCO in this disease is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The MARCO promoter SNP increased the risk for severe RSV disease by approximately 62%. A previous investigation tested whether 9 non-synonymous coding variants or tag SNPs in MARCO associated with chronic obstructive pulmonary disease and found no association, although one of the SNPs (rs41279766) associated with the risk of sepsis ( Thomsen et al, 2013 ). Another study found tag SNPs associated with increased risk of pulmonary tuberculosis, while another was associated with resistance ( Bowdish et al, 2013 ), thus the role of MARCO in this disease is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Although animal models using MARCO knockout mice strongly associate MARCO with many pulmonary infections, such as pneumonia and influenza [38-41], whether polymorphisms in MARCO are associated with susceptibility to infection in humans remains to be determined. A recent Danish study found that non-synonymous SNPs within MARCO were found at very low frequency (0.005-5%) within a Danish population, and in a study investigating whether MARCO was associated with chronic obstructive pulmonary disease (COPD) and lung infection in COPD patients, only one of these was associated with an increased risk of sepsis and none with pneumonia or COPD itself [42]. Unfortunately, the intronic SNPs identified in our study and in the Chinese Han population [23] were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have been centered on the role of MARCO in the host defense against respiratory tract infections and pneumoconiosis induced by crystalline silica or cigarette smoke (Thakur, Hamilton, & Holian, 2008; Thomsen, Nordestgaard, Kobzik, & Dahl, 2013). However, several lines of evidence recently implicated MARCO as a regulator of DC function and antitumor immunity.…”
Section: Scavenger Receptors In Cancer Immunobiologymentioning
confidence: 99%